Implementasi Manajemen Risiko Berbasis Syariah Pada Lembaga Keuangan Syariah - Mahirah Nurfadhilah, Nisrina; Fajrini Ridhati; Marsha Ananda Putri, Raden (Risalah Iqtisadiyah: Journal of Sharia Economics, Sharia Economics Study Program, STEI Ar Risalah Sumatera Barat, 2023)
The main objective of risk management is to identify, measure and manage the risks associated with the operational and financial activities of a bank or Islamic financial institution. This study uses a literature review research method. The process of data analysis begins with reducing the collected data into important data that is relevant to the research topic. The findings from this study are that Risk Management in Islamic Banking and Finance is important for identifying, measuring, managing and monitoring risks in order to minimize losses due to uncontrolled risks and ensure business continuity. Characteristics of Risk Management in Islamic Banking and Finance includes sharia principles that must be followed, namely fairness, sharing risks, and not harming other parties. Risk identification in Islamic Banking and Finance is carried out to identify the types of risks faced by Islamic financial institutions. Risk Monitoring and Evaluation in Islamic Banking and Finance is carried out to ensure that risks are controlled and in accordance with standards, so that Islamic financial institutions can minimize risks and ensure the continuity of their business.